Pemberdayaan Masyarakat Dusun Giling dalam Program Perilaku Hidup Bersih dan Sehat (PHBS) Sesuai Ajaran Islami - Abdau, Inas Muhammad; Milatia, Rizki Laila; Ru'iya, Sutipyo (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Clean and healthy living is a necessity for all humans to be happy in their lives. Not all communities can implement clean and healthy living methods. One of them is what happened in Giling Hamlet, Tuksono Village, Sentolo District, Kulon Progo Regency, Special Region of Yogyakarta Province, still needs to be optimized. Partners in this community service are the community in Giling Hamlet, Tuksono Village, Sentolo District. The community service method applied is counseling on Clean and Healthy Living Behavior in accordance with health theory and Islamic teachings. The results of the community service can help partners understand the meaning of Clean and Healthy Living Behavior delivered by the community service team. The material presented is very appropriate to the needs of partners to change their lifestyle towards a healthier life in accordance with health provisions and Islamic teachings. There are 95% of participants who feel that the community service is beneficial to themselves and the community, and 97% of participants feel that participants are satisfied with the implementation of the community service.